Immunoflourescent assessment of Herpes Simplex Virus (HSV) type 1 in oral lichen planus - Ali, Muthanna K (Journal of Baghdad College of Dentistry, 2014)
Background: Oral lichen planus is one of the most common dermatological diseases presenting in the oral cavity. Hence, viral infection of the oral mucosa may be involved in the pathogenesis of oral lichen planus, Taking in to consideration the oncogenic potential of HSV-1, this study aimed to assess the presence of Herpes Simplex Virus type one by direct immunoflourescent in oral lichen planus. This study aimed to assess the presence of HSV type1 by direct immunofluorescent in histopathologically diagnosed OLP Material and Method: Twenty formalin fixed embedded tissue blocks of oral lichen planus with 2 Positive control cases were taken from patients having infection with herpes labialis, US Biological herpes simplex virus-1 Glycoprotein C was used for detection of HSV-1 Ag by direct immunofluorescence assay Results: One case of oral lichen planus showed positivity of HSV 1 with a non- statistical significance. Conclusion: The present study couldn’t find any correlation between HSV-1 positivity with clinical and histopathological features of OLP.